Anxiety level modulates endocrine and neuromodulatory responses to maximal exercise and 24-h recovery in elite rowers - Ostapiuk-Karolczuk, J.; Dziewiecka, H.; Kasperska, A.; Cichon-Wozniak, J.; Reysner, M.; Gruszka, W.; Basta, P.; Kaczmarczyk, S.; Skarpanska-Stejnborn, A. (Frontiers in Physiology, 2025)
Introduction: Anxiety is a key psychological factor in competitive sport that interacts with physiological stress responses. By modulating neuroendocrine and neurotransmitter activity, it may influence how athletes adapt to maximal effort and recover afterward. The study addressed the gap in understanding how pre-exercise anxiety affects the recovery dynamics of these responses in elite endurance athletes.